Integrated Integrated Decision Support System for Student Academic Activities Using a Combination of AHP and SMART Methods - Nabila Salsabila; Muhammad Dedi Irawan (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Digital transformation in the world of education requires educational institutions to have an objective and integrated decision-making system. However, the results of observations at SMKN 13 Medan showed that there are still problems in the form of data fragmentation between departments which causes the process of determining outstanding students and selecting new students' majors to be inefficient and prone to subjectivity. This study aims to develop an integrated web-based Decision Support System (DSS) using a combination of the Analytic Hierarchy Process (AHP) and Simple Multi-Attribute Rating Technique (SMART) methods to improve accuracy and fairness in the academic decision-making process. The system development method used is Waterfall, with stages of analysis, design, implementation, testing, application, and maintenance. The results of quantitative calculations show that in determining outstanding students, student Amira obtained the highest score of 95.79, while in selecting majors, student Aulia Fatimah Al Zahra obtained the highest score of 86.11 and was recommended to the Computer and Network Engineering (TKJ) department. The system testing results show that the AHP-SMART combination successfully provides accurate and consistent results with a weighting consistency level of CR = 0.08 for achievement and CR = 0.06 for majors. It can be concluded that the developed system is able to integrate data across majors, improve assessment efficiency, and support transparent, objective, and data-based decision-making in the vocational school environment.